Factores que inciden en la tasa de desempleo en los países sudamericanos durante el periodo 2009-2017. - Cruz Granda, Jenniffer Katiuska; Reyes Cueva, Iliana Marisela (My University, 2021)
The purpose of this document is to determine and analyze the factors that infer within the unemployment rate in South America during 2009-2018, taking into consideration that the lack of employment is one of the main problems of greater relevance within the economy of the nations, for this reason great concern is generated within the social, political and economic environments, currently in South American countries due to the lack of policies that help to stop or control this problem. The applied methodology is descriptive with a quantitative approach within the data analysis, through the econometric analysis for panel data, it is proposed to explain the unemployment rate estimation model, the analysis of the texts and data obtained reflect that The factors that generate the greatest repercussion are linked to the political and economic administration due to the mismanagement of resources in the wealth generated by the country itself and the people within its social environment.
El propósito de este documento es determinar y analizar los factores que infieren dentro de la tasa de desempleo en Sudamérica durante el 2009-2018, tomando en consideración que la falta de empleo es uno de los principales problemas de mayor relevancia dentro de la economía de las naciones, por ello se genera gran preocupación dentro los entornos sociales, políticos y económicos, en la actualidad en los países sudamericanos debido a la falta de políticas que ayuden a detener o controlar este problema. La metodología aplicada es de tipo descriptivo con un enfoque cuantitativo dentro del análisis de los datos, mediante el análisis econométrico para datos de panel, se plantea explicar el modelo de estimación de la tasa de desempleo, el análisis de los textos y datos obtenidos reflejan que los factores que generan mayor repercusión están ligadas a la administración política, económica por el mal manejo de recursos en la riqueza generada por el mismo país y las personas dentro de su entorno social.
Keywords: DESEMPLEO; POBREZA; ENTORNOS ECONÓMICOS; ADMINISTRACIÓN